Insights into the mechanism of action of quinoline antimalarials against Plasmodium falciparum revealed by novel fluorescent analogues and chemical proteomics - Woodland, John Geoffrey (Department of Chemistry, 2017)
For centuries, quinoline-based drugs have formed the cornerstone of antimalarial treatment. Despite recent challenges posed by resistance, interest in these molecules persists. It is thus surprising that crucial details of their mechanism of action against the most virulent malaria parasite, Plasmodium falciparum, remain unresolved. This thesis develops new tools to generate deeper insights into the modes of action of the two major classes of the quinoline antimalarials against P. falciparum. These are the quinoline methanols, represented by the diastereomeric Cinchona alkaloids quinine and quinidine, and the 4-aminoquinolines, represented by chloroquine. Mechanistic studies of these antimalarials have typically focused on the inhibition of haemozoin biocrystallisation within the acidic digestive vacuole of P. falciparum. In order to conduct a comprehensive survey of the subcellular localisation of these antimalarials across the entire infected erythrocyte, a suite of novel fluorescent derivatives was designed and synthesised. Key physicochemical properties of these antimalarials were retained in order to preserve the interactions of these drugs with their putative target, ferriprotoporphyrin IX or Fe(III)PPIX. Versatile derivatisation of the alkaloids was enabled by a regioselective radical-mediated thiolene click reduction. 7-Nitrobenz-2-oxa-1,3-diazole (NBD) was identified as a suitable reporter fluorophore and was attached to the quinoline core by nucleophilic aromatic substitution. The length of the spacer chain between the quinoline and the fluorophore was varied by preparing NBD-labelled amino acids and their corresponding succinimidyl esters. A novel NBD-labelled chloroquine derivative was prepared by using its N-dealkylated analogue as a key intermediate. A single quinine derivative with an alternative fluorophore, bimane, was also prepared.